THE ISSUE OF THE UNTOUCHABLES AND ITS POWER RELATIONS IN ARUNDHATI ROY'S THE GOD OF SMALL THINGS WITHIN A POSTCOLONIAL FRAMEWORK - Annisa Rizkia Utami, - (2008)
This paper entitled The Issue of the Untouchables and Its Power Relations in Arundhati Roy's the God of Small Things within a Postcolonial Framework. The study focuses on the issue of power relations in the caste system in India; and therefore, the power is negotiated between the Touchables and the Untouchables. This study is constructed within postcolonial framework and ideas of power by Foucault as the tools to analyze the exercise of power in the novel. The method applied in conducting the research is qualitative approach in the form of a descriptive method. By using this method, the writer attempted to define and describe data collected. The data are taken from the relationships of power between the Touchables and the Untouchables found in the novel. The findings of the analysis show that the types of power are classified into societal power, institutional power, knowledge power, disciplinary power, and repressive power. Meanwhile, the exercise of power brings about resistance in forms of protest and refusal. The outcomes of power relations to the Untouchables result in discrimination and resistance. The writer came to a conclusion that power is omnipresent as everyone could have power even though they are inferior in society. Power is not the poverty of one self, a structure, or a class; rather, it is inherent in individuals. Therefore, sometimes there is time when a character is inferior but has power to control over others. Finally, in raising the issue of the Untouchables, we would raise our sympathy for people whose existence is almost forsaken by the society. Besides, we would increase our sensibility for those who do good turn in our lives, but somehow we considered these people as just 'small things' - unimportant.